China's Growth : Can Goldilocks Outgrow Bears? - Maliszewski, Wojciech; Zhang, Longmei (Washington, D.C. : International Monetary Fund, 2015)
The paper analyzes the recent growth dynamics in China, evaluating both cyclical positions and long-term growth prospects. The analysis shows that financial cycles play a more important role than traditional inflation-based cycles in shaping the dynamics of growth. Currently, the 'finance-neutral' gap-our measure of the financial cycle-is large and positive, reflecting imbalances accumulated in the economy since the Global Financial Crisis. A period of slower growth is therefore both likely and needed in the near term to restore the economy to equilibrium. In the medium term, growth will slow as China moves closer to the technology frontier, but a steadfast implementation of reforms can ensure that China follows the path of the 'Asia Tigers' and achieves successful convergence to high-income status.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet